Changes in glycaemic control, blood pressure and lipids 5 years following laparoscopic adjustable gastric banding combined with medical care in patients with type 2 diabetes: a longitudinal analysis. Issue 3 (4th March 2018) - Mistry, P.; Currie, V.; Super, P.; le Roux, C. W.; Tahrani, A. A.; Singhal, R.
Summary: The long‐term outcomes of weight loss maintenance induced by laparoscopic adjustable gastric band (LAGB) followed by multidisciplinary medical care in patients with type 2 diabetes mellitus (T2DM) (beyond 3 years) are scarcely reported. Study aims were to determine the longer term metabolic outcomes following LAGB combined with medical care in patients with T2DM. This is a longitudinal analysis of 200 adults with T2DM who had LAGB between 2003 and 2008 and were followed up till 2013 at a single bariatric unit in a tertiary UK centre. A total of 200 patients (age 47 ± 9.7 years; body mass index [BMI] 52.8 ± 9.2 kg m −2 ; glycosylated haemoglobin (HbA1c) 7.9 ± 1.9% [62.8 mmol mol −1 ]; women, n  = 123 [61.5%]; insulin treatment, n  = 71 [35.5%]) were included. The mean follow‐up was 62.0 ± 13.0 months (range 18–84 months). There were significant reductions in body weight (−24.4 ± 12.3% [38 ± 22.7 kg]), HbA1c (−1.4 ± 2.0%), systolic blood pressure [BP] (−11.7 ± 23.5 mmHg), total cholesterol and triglyceride levels. The proportion of patients requiring insulin reduced from 36.2% to 12.3%. The overall band complication rate was 21% (21 patients). LAGB when combined with multidisciplinary medical care significantly improved metabolic outcomes in patients with T2DM independent of diabetes duration, and baseline BMI over 5 years. Diabetes duration and baseline BMI did not predict changes in glycaemic control, BP or lipids following LAGB.